A Question of Love and Trust? The Role of Relationship Factors in Adolescent Sexual Decision Making. Issue 8 (October 2015) - Feldstein Ewing, Sarah W.; Bryan, Angela D.
ABSTRACT: Objective: While representing only 25% of the sexually active population, 50% of all new sexually transmitted infections occur among young people mostly because of inconsistent condom use. Critically, the majority of adolescent sexual activity takes place in the context of romantic relationships; thus, it is important to understand how relationship factors may influence decision making about the use of protection. Methods: We used a mixed-method approach to investigate the extent to which relationship length, degree of trust or love in the relationship, and frequency of intercourse influence both perceptions of the probability of condom use and self-reported condom use in the context of relationships among a diverse sample of high-risk adolescents (age 12–19 yr). Results: Participants were least likely to use condoms if they were in relationships with high trust or love and high frequency of intercourse. Importantly, sexual experience status was a strong moderator of primary effects. Conclusion: The perspective of motivated cognition provides a useful theoretical framework to better understand adolescent decision making about condom use, particularly for sexually experienced youth.